Analysis and Design of Administrative Data Management Using an Elicitation Approach (Case Study: LKP Putra Putri Indonesia) - Arif Saripudin; Cecep Kurnia Sastradipraja; Falentino Sembiring (Unversitas Muhammadiyah Mataram, 2020)
This research aims to analyze and design an administrative data management information system in LKP3I, which currently manages it is still manual, namely using Ms. Excel office tools, so it often experiences problems such as accumulation of documents, difficulty finding data, and scattered data of course participants. The application development process using the waterfall model includes collecting data and information, at the analysis stage using the elicitation approach technique which is represented by system modeling, namely flow maps, context diagrams, and data flow diagrams. Construction of web-based application systems using the programming languages VB.Net and Ms. Access as database management system, testing and evaluating the feasibility of the system using the BlackBox and group discussions. Based on the results of the research and system evaluation conducted, the prototype of the LKP3I administrative data management system that was built through the elicitation approach received a fairly good assessment, which proves that the hypothesis in this study has been tested. Respondents can receive the results of the information system prototype that will be implemented with the provision of improved specifications and functions of user requirements.